What Legitimizes Segregation? The Context of Special Education Discourse: A Response to Ryndak et al. (June 2014) - Jackson, Lewis
Ryndak and colleagues provide a strong case that progress toward more and better access to general education is not occurring for students with intellectual disabilities. This response to their paper begins by agreeing with their assessment of our current situation, then it offers one possible reason for this state of affairs: the discourse that occurs when special education teams are planning outcomes and instruction for these students discourages the use of grade-level curriculum and general education classrooms. Part of the problem is that the discourse preserves segregation through a planning terminology that is inconsistent with how all other students in a school are assessed and described. However, it is also argued that a major property of this discourse is a misguided emphasis on "functional skills, " and that this emphasis contributes to our lack of progress in achieving access to general education curriculum and settings. A related argument is also made that the educational goal development process that typically occurs within special education discourse derives student outcomes from varied skill sources that, collectively, do not offer the structure and coherency of a real curriculum. This process, justified at least in part by interpretations of individualization, may also be impeding our movement toward greater alignment with general education for these students. A case is made for school districts establishing policies that require the use of grade-level general education curriculum with these students. Potential issues and concerns related to individualization, content standards, curriculum adaptation, and progress monitoring are discussed.